In Situ Gelling Formulation of Naproxen for Oral Sustained Delivery System - S.Yousif, Hala; I. Khalil, Yehia (Iraqi Journal of Pharmaceutical Sciences, 2017)
Naproxen is non-steroidal anti-inflammatory drug, which has antipyretic and anti-inflammatory effect. It is extensively bound to plasma albumin, and exhibits gastric toxicity, so it may be more efficient to deliver the drug in its sustained release dosage form and adequate blood level is achieved. Three liquid formulations with in situ gelling properties have been assessed for their potential for the oral sustained delivery of naproxen . The formulations were dilute solutions of: (a) pectin; (b) gellan gum and; (c) sodium alginate, all containing complexed calcium ion that form gels when these ions are released in the acidic environment of the stomach . The viscosity of the sols and drug release were measured, and was found to be dependent on the type and concentration of the gelling agent. Pectin sol shows the highest viscosity and drug release . The influence of variation of gastric pH and the effect of added 1.6 mM Ca++ ions on the gelation property and the release profile of the liquid formulations were examined. The efficiency of gelation was significantly reduced with increase of pH. In addition the influence of different concentrations of sorbitol were determined .The results showed that 10% w/v sorbitol is the best concentration that maintained fluidity and ease of administration for the selected formula . The selected formula was examined for its stability and expiration date, and, it was found that there was no evidence of physical changes under experimental conditions, with estimated expiration of about 4.1 years and pH of the formula stated at 5.1.Key word: naproxen, in situ gelling, oral preparations, gel.